Impact of Complete Denture and Mandibular Advancement Device in the Management of Completely Edentulous Obstructive Sleep Apneic Individuals: A Systematic Review with Meta-Analysis - Preetha Krishnamurthy; Fathima Raza; Anand Kumar Vaidyanathan (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Obstructive sleep apnea (OSA) is an underdiagnosed and potentially serious disorder that is accentuated by edentulism. The overclosure of the mandible and a potential upper airway collapse during sleep creates challenges in treating edentulous sleep apneic patients.Purpose: To evaluate complete dentures and mandibular advancement devices as potential oral appliances in the management of sleep apnea in completely edentulous patients.Materials and Method: The study design was a systematic review with meta-analysis. The search criteria complied with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and the keywords in population, intervention, control, and outcomes (PICO) format was systematically searched for relevant research articles published till August 2021 in an electronic database (PubMed, Cochrane, Science Direct, Ovid). Randomized controlled trials and cohort studies were included that compared the effectiveness of oral appliances on apnea-hypopnea index (AHI), airway space, and quality of sleep in edentulous sleep apneic patients.Results: 1785 articles were derived from the initial search and based on inclusion criteria, 10 articles were systematically filtered for qualitative analysis and assessed for risk of bias using the Cochrane risk of bias tool and ROBINS-I tool. Out of the 10 articles, 5 articles were taken for quantitative analysis. The use of a mandibular advancement device (MAD) showed a decrease in AHI score, but the available data was heterogeneous to conduct a meta-analysis. The mean difference of AHI for the random effect model between the non-complete denture and complete denture wearers at sleep was -0.49[95% CI (-1.47,0.48)] events per hour, but the change was non-significant (p>.05).Conclusion: The complete dentures as an oral appliance had reduced apneic episodes in completely edentulous sleep apneic patients, but the effectiveness cannot be solely attributed to the prosthesis in the treatment of OSA. MAD showed greater improvement in reducing AHI, however, the level of evidence was inadequate to provide a conclusive statement.